Reliability and Validity of the Korean Version of the Infant-Toddler Social and Emotional Assessment - Lee, Kyung Sook (Psychiatry Investig, 2018)
OBJECTIVE: This article examined the psychometric properties of the Korean version of the Infant-Toddler Social and Emotional Assessment (K-ITSEA). METHODS: Translation and back-translation of the K-ITSEA were conducted after obtaining a permission. Two thousand two hundred thirty six Korean community infants (1,199 boys and 1,037 girls) between the ages of 12 and 36 months (M=34.23, SD=3.80) and 90 clinical infant samples (60 boys and 30 girls) between the ages of 12 and 36 months (M=26.84, SD=6.24) participated in the present study. RESULTS: Confirmatory factor analyses supported the Internalizing, Externalizing, Dysregulation, and Competence domains as well as the 17 individual scales that comprise the K-ITSEA. Young children’s sex and age differences emerged for some problem and most competence scales. All domains showed adequate intrascale reliability and test-retest reliability. Scale intracorrelation analyses and associations between the K-ITSEA and Korean version of PSI, Korean version of CBCL1.5-5 supported the validity of the assessment. Comparisons of the K-ITSEA scores for the Autism Spectrum Disorder, Psychiatric Disorders and Matched control groups supported the discriminant validity of the K-ITSEA. CONCLUSION: This preliminary results indicate that the K-ITSEA would be a useful assessment for detecting the early childhood’s behavior problems and competences in Korean population.